2011
DOI: 10.1111/j.1540-6237.2011.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Political Threat and Immigration: Party Identification, Demographic Context, and Immigration Policy Preference*

Abstract: Objective. I propose that the effect of partisanship on views on immigration is context dependent. I argue that Republicans in counties experiencing high levels of immigration are more likely to support new immigration restrictions in contrast to Democrats and Independents than Republicans in counties with a relatively small foreign‐born population, and I suspect this is the case because Republicans in high‐immigration counties feel politically threatened by the foreign‐born residents, who are more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 39 publications
1
64
1
Order By: Relevance
“…When contextual threat has referenced country of origin (e.g., percent foreign born) results have shown little relationship to immigration policy preferences (Hawley 2011;McLaren 2003;Sides and Citrin 2007). One exception provided by Hood and Morris (1998) found more opposition to increased immigration in relation to levels of undocumented immigrants and less opposition related to legal immigrants.…”
Section: Contextual Threatmentioning
confidence: 88%
See 4 more Smart Citations
“…When contextual threat has referenced country of origin (e.g., percent foreign born) results have shown little relationship to immigration policy preferences (Hawley 2011;McLaren 2003;Sides and Citrin 2007). One exception provided by Hood and Morris (1998) found more opposition to increased immigration in relation to levels of undocumented immigrants and less opposition related to legal immigrants.…”
Section: Contextual Threatmentioning
confidence: 88%
“…Results provide only limited support for the threat hypothesis. M. V. , Justin Allen Berg (2009), andGeorge Hawley (2011) all reported null findings. Louise Campbell and colleagues (2006) found that percent Hispanic significantly influenced opposition to one of three California initiatives-Proposition 187 limiting public services for immigrants.…”
Section: Contextual Threatmentioning
confidence: 91%
See 3 more Smart Citations